Composition of Gingerbread Fretwork: Case Studies of Chanthaboon Waterfront Community - Phueaknamphol, Kanlayanee; Joneurairatana, Eakachat; Sirivesmas, Veerawat (NAJUA: History of Architecture and Thai Architecture, 2024)
The gingerbread pattern refers to ornate, perforated wooden carvings with curved motifs, commonly used to embellish architectural elements such as gables and balconies. This style gained considerable popularity during the reign of Queen Victoria of England (1837-1901). Architects designed countryside summer palaces in harmony with nature, incorporating gingerbread patterns into the buildings to evoke a sense of relaxation and softness. These patterns, influenced by Gothic art seen in cathedral decorations, feature distinct motifs such as tulips, spiraling vines, geometric shapes, and teardrop designs1. The introduction of gingerbread patterns in Thailand began during the reign of King Rama V, who visited Europe, a period when British and French artisans were also arriving in Siam. This led to a transformation in building styles and architectural ornamentation, with many European-style buildings emerging, initially in Bangkok before spreading to other regions. In Thailand’s southern region, ingerbread patterns reflect a blend of Islamic artistic influences from Penang, Malaysia. In the northern region, some gingerbread designs were influenced by Burmese art. In the eastern cities, such as Chanthaburi, which was under French occupation for 11 years, gingerbread patterns are also prominently found within the town center2. Gingerbread patterns in Thailand are commonly found in areas where community administration centers are located, as well as in foreign residences or commercial hubs. These patterns requently adorn the houses of the royal family, government buildings, affluent residences, and monastic dwellings. This research explores the gingerbread fretwork patterns found in the Chanthaboon Waterfront Community, Chanthaburi Province, Thailand. This community is known for its cultural history and unique architecture, featuring traditional houses that blend Thai, Chinese, Vietnamese, and French influences3. This study aims to document, classify, and analyze the gingerbread fretwork patterns on these houses to preserve and understand the community’s artistic heritage before it deteriorates further. The research employs qualitative methods, including field surveys, interviews, photographic documentation, and analysis of existing literature. In selecting case studies, the focus was limited to houses situated in the Chanthaboon Waterfront Community with exterior gingerbread fretwork that remains intact and in good condition. The findings reveal that 15 houses along Sukhaphiban Road in the Chanthaboon Waterfront Community are decorated with gingerbread fretwork, with a total of 26 distinct patterns identified. The gingerbread patterns, often used in architectural features such as eaves, doors, windows, and balconies, not only enhance the visual appeal of the structures but also serve functional purposes, such as ventilation. These designs, primarily floral and geometric motifs, were found in various architectural elements. The study categorized these patterns into three main types: attached, detached, and mixed—based on their design and carving techniques. The findings indicate that the gingerbread fretwork in the Chanthaboon Waterfront Community is influenced by Victorian and Gothic styles but has been adapted to the local environment and aesthetic preferences. This unique fusion reflects the diverse cultural background of the area.